BIOLOGICAL ACTIVITY AND MOLECULAR DOCKING OF 2’-BROMO-4-METHOXY-3-NITRO BENZIL, 2,2’-DIBROMO BENZIL, AND 4,4’-DICHLORO BENZIL - G, Nithya; R, Sudha; Kanakam, Charles C (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A series of benzil compounds have been synthesized by oxidation of corresponding benzoins which in turn were prepared from respective aldehydes. Using this protocol, three new benzils were prepared in good-to-excellent yields and their biological activity has been delineated. Methods: Molecular docking studies were conducted to validate the obtained pharmacological data and to provide understandable evidence for the observed antimicrobial activity of all synthesized compounds. Several benzils exhibited excellent antimicrobial and cytotoxic activity. To determine the cytotoxic effects, we used an MTT viability assay. Results: The results showed that cell growth is significantly lower in extract-treated cells compared to untreated control. The effect of inhibition of cell growth was shown in different concentration dosages for cytotoxic, antibacterial, and antioxidant activity in vitro. Discussion: The antimicrobial activity results indicated that some of the tested compounds showed the most promising antibacterial activities. These observations may promote a further development of our research in this field. The antioxidant activity was also performed for the compound benzil and its substituted analogs.